The Effect of Service Quality And Complaint Handling on Cutomer Loyality of Bank Syariah Indonesia Regional IV Jakarta 1 - Assudaisy, Abd Jabbar; Fa’uzobihi, Fa’uzobihi; Supriyadi, Supriyadi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Bank Syariah Indonesia (BSI) is the result of the merger of three Islamic banks, namely BRI Syariah, Bank Mandiri Syariah, and BNI Syariah, which became a new entity. The availability of various Islamic bank products such as services and products, makes Islamic banks a credible financial system that can be enjoyed by all levels of society. However, problems in terms of service often occur in the implementation of financial activities. This problem can cause complaints from customers. Customer complaints usually develop when the customer's impression of the desired service is different from what is expected. The objectives of this study are 1) To determine the quality of service to customer loyalty of all Bank Syariah Indonesia Branches under the coordination of Region IV Jakarta 1. 2) To determine the handling of complaints against Bank Syariah Indonesia customer loyalty in all branches under the coordination of Region IV Jakarta 1. 3) To determine the quality of service and handling of complaints simultaneously on the loyalty of Bank Syariah Indonesia customers in all branches under the coordination of Region IV Jakarta 1. The research method used is the correlation method with quantitative research type. The research results are as follows: 1) Based on the results of regression analysis partially customer loyalty has a significant effect on service quality, this is indicated by the Sig value. customer loyalty variable is smaller than  or 0.000 <0.05. 2) Based on the results of partial regression analysis, it is concluded that Complaint Handling has a significant effect on service quality, this is indicated by the Sig value. the Complaint Handling variable is smaller than  or 0.000 <0.05. 3) Based on the results of the coefficient of determination test, it is concluded that customer loyalty and Complaint Handling jointly affect service quality by 97.5% while the remaining 2.5% is influenced by other factors outside this research model, then from the results of the F test it is concluded that customer loyalty and Complaint Handling jointly affect service quality because the Sig. value is smaller than  or 0.000 <0.05.